Análise comparativa entre os livros didáticos para ensino de Inglês em Ensino Médio e a Proposta Curricular da SEDUC-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
Teaching English language in Brazil is regulated by Law 9,394 of 1996, also known as the Basic Education Guidelines and Bases Law (LDB), complemented by the National Curricular Parameters (NCP) for Foreign Language in Secondary Education, 1999. State Department of Education and Quality of Education - SEDUC-AM regulates the teaching of English in public schools, through the Curricular Proposal of English Language for High School, 2012. One of the didactic materials used in public schools is the collection of the "Take Over" book from the National Textbook Program (PNLD). Although the two materials follow the guidelines of the LDB and the NCPs, some teachers at the state public network find some mismatch at the time of planning classes, which motivated the accomplishment of this research, whose objective is to make the comparative analysis between both materials. The theoretical contribution of the research was anchored in the assumptions of the official documents and authors that are a reference in linguistic policies, approaches, methodologies and theories of teaching English as a foreign language, teachers formation and textbook. This study is a qualitative bibliographical research. After doing the comparative analysis between the transversal themes suggested in the two documents, the contents, the development of communicative skills and the theoretical assumptions of each one, the results indicated that the greater mismatch between them is in the thematic of the texts to be approached in the classroom as transversal topics, in the sequence in which the contents must be addressed, and in the communicative skills, rather than in the reading of texts in the English language, to be developed by the students, which allows us to conclude that both documents seem to need an update. Meanwhile, there is a great agreement between the theoretical assumptions of the two documents and the development of reading skill, which demonstrates that the focus of teaching English at High School in State public schools is in the activities of reading comprehension in English, although it is recommended that among the topics suggested, the socio-economic-cultural context of the students of the state public network should be addressed, so that the readings are really meaningful. At the end of the study, it is emphasized the importance of the initial and continuing teacher formation process, especially with regard to the use of textbooks, the creation of a research group related to textbooks, and the teaching of English as a foreign modern language, in the schools of the state public network, within an instrumental approach.
Keywords: Ensino de inglês; Proposta curricular; Livro didático; LINGUÍSTICA, LETRAS E ARTES: LETRAS